ANALISIS PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPERCAYAAN PELANGGAN SEBAGAI INTERVENING (Studi Pada Mahasiswa Undip Pengguna Smartphone Sony) - Al Ijie, Angga Luthfy; Santosa, Suryono Budi (Diponegoro Journal of Management, 2015)
Competition in an increasingly competitive smartphone industry resulted in a decrease in market share occurred at Sony smartphones in the period 2013-2014. This study aims to investigate the influence of brand image and product quality on purchasing decisions by customers trust Sony smartphone.The total sample of 100 respondents Sony smartphone users on student Undip. Data obtained from questions by using a questionnaire consisting of closed and open questions. Answer of respondents were analyzed with two-stage regression analysis tools SPSS (Statistical Package for Social Science).Based on the analysis conducted that the brand image and product quality positive effect on customer trust with a regression coefficient Y1= 0,343 X1+ 0,429 X2. While customer trust positive effect on purchasing decisions with a regression coefficient Y2 = 0,559 Y1.